Transcriptome analysis reveals pathogenesis-related gene 1 pathway against salicylic acid treatment in grapevine (Vitis vinifera L) - Rahman, Faiz Ur; Khan, Irshad Ahmad; Aslam, Ali; Liu, Ruitao; Sun, Lei; Wu, Yandi; Aslam, Muhammad Muzammal; Khan, Asad Ullah; Li, Peng; Jiang, Jianfu; Fan, Xiucai; Liu, Chonghuai; et al. (Frontiers in Genetics, 2022)
Salicylic acid (SA) is a well-studied phenolic plant hormone that plays an important role in plant defense against the hemi-biothrophic and biothrophic pathogens and depends on the living cells of host for the successful infection. In this study, a pathogenesis test was performed between Vitis davidii and V. vinifera cultivars against grape white rot disease (Coniella diplodiella). V. davidii was found to be resistant against this disease. SA contents were found to be higher in the resistant grape cultivar after different time points. RNA-seq analysis was conducted on susceptible grapevine cultivars after 12, 24, and 48 h of SA application with the hypothesis that SA may induce defense genes in susceptible cultivars. A total of 511 differentially expressed genes (DEGs) were identified from the RNA-seq data, including some important genes, VvWRKY1/2, VvNPR1, VvTGA2, and VvPR1, for the SA defense pathway. DEGs related to phytohormone signal transduction and flavonoid biosynthetic pathways were also upregulated. The quantitative real-time PCR (qRT-PCR) results of the significantly expressed transcripts were found to be consistent with the transcriptome data, with a high correlation between the two analyses. The pathogenesis-related gene 1 (VvPR1), which is an important marker gene for plant defense, was selected for further promoter analysis. The promoter sequence showed that it contains some important cis-elements (W-box, LS7, as-1, and TCA-element) to recruit the transcription factors VvWRKY, VvNPR1, and VvTGA2 to express the VvPR1 gene in response to SA treatment. Furthermore, the VvPR1 promoter was serially deleted into different fragments (−1,837, −1,443, −1,119, −864, −558, −436, and −192 ) bp and constructed vectors with the GUS reporter gene. Deletion analysis revealed that the VvPR1 promoter between −1837 bp to −558 bp induced significant GUS expression with respect to the control. On the basis of these results, the −558 bp region was assumed to be an important part of the VvPR1 promoter, and this region contained the important cis-elements related to SA, such as TCA-element (−1,472 bp), LS7 (−1,428 bp), and as-1 (−520 bp), that recruit the TFs and induce the expression of the VvPR1 gene. This study expanded the available information regarding SA-induced defense in susceptible grapes and recognized the molecular mechanisms through which this defense might be mediated.